Evaluation of AI tools as a financial risk mitigator : A case study on Emplifi - Soldatova, Valeriya (2025)
This thesis analyses the role of artificial intelligence tools in financial risk management at mid-sized technology companies, using Emplifi as a case study. Combining both theoretical and practical approaches, it examines tools such as explainable AI, predictive analytics, generative AI, sentiment analysis, and provides an overview of AI regulatory standards. The aim is to provide a practical framework for AI adoption in mid-sized SaaS companies. The foundation of this research is a semi-structured expert interview, complemented by five benchmark industry reports. Analysis of this data reflects Emplifi’s current risk management practices and its readiness for AI implementation. The findings demonstrate that although Emplifi has not yet integrated AI tools into its internal processes, it sets the stage for future development. This research highlights potential benefits while addressing obstacles and organizational barriers companies may face when introducing AI-driven risk mitigation strategies. The study contributes to the literature by exploring the practical nuances of AI adoption in mid-sized SaaS environments.